On Strength of Brittle Nanomaterials: Confinement Effect on Weibull Distributions - Shin, Dahye; Jang, Dongchan (Frontiers in Materials, 2019)
Recent progress in nanotechnology enables us to utilize elastic strain engineering, the emerging technology capable of controlling the physio-chemical properties of materials via externally-imposed elastic strains, for hard materials. Because the range of properties accessible with elastic strains are set by materials’ elasticity limits, it is of great importance to suppress the occurrence of any inelastic deformations and failure, and thus the fundamental knowledge on fracture behavior at nanoscale is highly required. The conventional Weibull theory, which has been widely used for last the few decades to explain the failure statistics of brittle bulk materials, has a limitation to be directly applied to samples of nanometer dimensions because the baseline assumption on statistical equivalence becomes intractable for small samples. In this study, we suggest an integrated equation presenting the sample size effect on fracture strength for brittle nanomaterials by further considering the confinement of the flaw size distribution. This new approach is applicable to any homogeneous brittle nanomaterial whose failure is governed by linear elastic fracture mechanics and shows good agreement with experimental data collected from the literature. We expect that this theoretical study offers a new guideline to employ brittle nanomaterials in designing and fabricating the advanced strain engineering system.